Modulation effects of Dendrobium officinale on gut microbiota of type 2 diabetes model mice - Wang, Sai; Li, Xin-Yu; Shen, Liang (FEMS microbiology letters, 2021)
Abstract In recent years, the relationship between type 2 diabetes (T2D) and gut microbiota has attracted much interest. Dendrobium officinale is a valuable traditional Chinese medicine (TCM) with anti-T2D potential, while its action mechanism remains to be further studied. This study was designed to investigate the modulation effects of D. officinale on gut microbiota of T2D model mice to provide clues to its pharmacology by high-throughput sequencing techniques. It was found that D. officinale supplement could significantly reduce the fasting blood glucose levels of T2D mice. Dendrobium officinale supplement could modulate the composition of gut microbiota and increase the relative abundances of key bacterial taxa associated with T2D development, including Akkermansia and Parabacteroides. Compared with placebo group mice, several Kyoto Encyclopedia of Gene and Genomes pathways associated with T2D altered in the D. officinale treated group. These findings indicated the modulation of D. officinale on gut microbiota of T2D mice, which provide potential pharmacological implications. The regulation of gut microboita might make important contribution to the anti-type 2 diabetes effect of the traditional medicine D. officinale.